Determinants of Physical and Mental Health-related Quality of Life among Patients with Breast Cancer During COVID-19 Pandemic - Jamil, Mohd; Merdawati, Leni; Krisdianto, Boby Febri; Khambri, Daan; Harahap, Wirsma Arif; Arifin, Hidayat (Department of Nursing, Faculty of Medicine, Universitas Diponegoro, 2023)
Background: The concern surrounding the physical and mental health-related quality of life (HRQoL) among patients with breast cancer emerged during COVID-19. However, there is a lack of sufficient studies that have specifically addressed this issue. It is crucial to emphasize the evaluation of this aspect as it significantly impacts the enhancement of future physical and mental HRQoL for these patients.Purpose: This study investigated the determinants of physical and mental HRQoL among patients with breast cancer during COVID-19.Methods: In a cross-sectional study conducted between September and October 2022, participation involved 260 patients diagnosed with breast cancer, selected through convenience sampling. Our observation focused on assessing the outcomes of physical and mental HRQoL using the Short Form (SF-12) questionnaire for data collection. Additionally, the data underwent analysis via binary logistic regression.Results: Respondents aged <50 years (p=0.010; aOR=2.08; 95% CI=1.18–3.67), unemployed (p=0.022; aOR=2.29; 95% CI=1.16–4.53), and had high depression (p=0.026; aOR=2.41; 95% CI=1.13–5.12) have a more likelihood to have low physical HRQoL. In addition, unemployed respondents (p=<0.001; aOR=4.15; 95% CI=2.14–8.04) and had high anxiety (p=0.004; aOR=2.71; 95% CI=1.38–5.33) have more likelihood to have low mental HRQoL.Conclusion: In this study, it was found that anxiety, depression, and unemployed respondents were associated with a higher likelihood of experiencing lower physical and mental HRQoL. Nurses and healthcare workers should prioritize addressing psychological issues such as anxiety and depression among breast cancer patients, emphasizing the necessity for interventions aimed at alleviating these concerns.